Space-Time Continuous Models of Swarm Robotic Systems Supporting Global-to-Local Programming - Hamann, Heiko; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
In this book, a genericmodel in as far as possiblemathematical closed-formis developed that predicts the behavior of large self-organizing robot groups (robot swarms) based on their control algorithm. In addition, an extensive subsumption of the relatively young and distinctive interdisciplinary research field of swarm robotics is emphasized. The connection to many related fields is highlighted and the concepts and methods borrowed from these fields are described shortly.
and Purpose -- Fundamentals of Swarm Robotics - An Interdisciplinary Approach -- State-of-the-Art in Modeling and Design of Swarms -- A Framework of Models for Swarm Robotic Systems -- Validation by Results of Experiments and Simulations -- Conclusion and Outlook.
Keywords: Engineering; Artificial intelligence; Physics; Consciousness; Engineering; Robotics and Automation; Artificial Intelligence (incl. Robotics).; Complexity; Computational Intelligence; Cognitive Psychology